Healthcare resource use and costs of severe, uncontrolled eosinophilic asthma in the UK general population. Issue 2 (16th September 2017) - Kerkhof, Marjan; Tran, Trung N; Soriano, Joan B; Golam, Sarowar; Gibson, Danny; Hillyer, Elizabeth V; Price, David B
Abstract : Background: Little is known about the prevalence of severe, uncontrolled eosinophilic asthma (SUEA) and associated costs. Aims: We sought to determine the prevalence of SUEA and compare asthma-related healthcare resource use (HCRU) and associated costs with overall means for a general asthma population. Methods: This cohort study evaluated anonymised medical record data (December 1989 through June 2015) from the Clinical Practice Research Datalink and the Optimum Patient Care Research Database to study UK patients with active asthma (diagnostic code and one or more drug prescriptions in the baseline year), aged 5 years and older, without concomitant COPD, and with recorded eosinophil count. SUEA was defined as two or more asthma attacks during 1 baseline year preceding a high blood eosinophil count (≥0.3×10 9 /L) for patients prescribed long-acting β2 -agonist (LABA) and high-dosage inhaled corticosteroids (ICS) during baseline plus 1 follow-up year. We compared asthma-related HCRU and associated direct costs (2015 pounds sterling, £) during the follow-up year for SUEA versus the general asthma population. Results: Of 363 558 patients with active asthma and recorded eosinophil count, 64% were women, mean (SD) age was 49 (21) years; 43% had high eosinophil counts, 7% had two or more attacks in the baseline year and 10% were prescribed high-dosage ICS/LABA for 2 study years. Overall, 2940 (0.81%; 95% CI 0.78% to 0.84%) patients had SUEA. Total mean per-patient HCRU and associated costs were four times greater for SUEA versus all patients (HCRU and cost ratios 3.9; 95% CI 3.7 to 4.1). Conclusions: Less than 1% of patients in a general asthma population had SUEA. These patients accounted for substantially greater asthma-related HCRU and costs than average patients with asthma.